(untitled) (Pakistan Journal of Engineering, Technology and Science, 2025)
methodologies has gained significant attention in producing user-centric products. Feature-driven development incorporates market demands in a very short period and accomplishes outcomes and interpretations from each iteration. Whereas design thinking is a human-centered approach that keeps the user at the core of the decision. This research aims to propose a framework that establishes a bridge between feature-driven development and design thinking, as user needs are not prioritized during feature-driven development due to the main emphasis on feature completion, and to enhance user-centered feature delivery in agile environments. This research investigates the 40 respondents’ opinions, consisting of low-experienced and highly experienced practitioners, drawing on a mixed-methods research design that includes surveys with agile teams. We explore the proposed framework’s effects on user specifications, speculation, differentiation, data dissemination, emotional engagement, level of fidelity, user-centric experience, co-creation, realism, and user contentment. The analysis revealed that user satisfaction is influenced by experience levels, with years of experience showing a significant main effect (p = 0.024). Low-experienced individuals had lower satisfaction scores compared to high-experienced individuals. These findings suggest that experience duration plays a key role in shaping user satisfaction. A mean difference of -0.170 indicates lower user satisfaction among less experienced individuals, suggesting that satisfaction varies with experience duration. These findings suggest that variations in user satisfaction are influenced by the duration of experience.